Selective Extraction of Americium(III) over Europium(III) Ions with Pyridylpyrazole Ligands: Structure–Property Relationships. Issue 3 (23rd January 2017) - Su, Dongping; Liu, Ying; Li, Shimeng; Ding, Songdong; Jin, Yongdong; Wang, Zhipeng; Hu, Xiaoyang; Zhang, Lirong
Abstract : To clarify the structure–property relationships of pyridylpyrazole ligands and provide guidance for the design of new and more efficient ligands for the selective extraction of actinides over lanthanides, a series of alkyl‐substituted pyridylpyrazole ligands with different branched chains at different positions of the pyrazole ring were synthesized. Extraction experiments showed that the pyridylpyrazole ligands exhibited good selective extraction abilities for Am III ions, and the steric effects of the branched chain had a significant impact on the distribution ratios of Am III and Eu III ions as well as the separation factor. Moreover, both slope analyses and UV/Vis spectrometry titrations indicated the formation of a 1:1 complex of 2‐(1‐octyl‐1 H ‐pyrazol‐3‐yl)pyridine (C8‐PypzH) with Eu III ions. The stability constant (log K ) for this complex obtained from the UV/Vis titration was 4.45 ± 0.04. Single crystals of the complexes of 3‐(2‐pyridyl)pyrazole (PypzH) with Eu(NO3 )3 and Sm(NO3 )3 were obtained; PypzH acts as a bidentate ligand in the crystal structures, and the N atom with a bound H atom did not participate in the coordination. In general, this study revealed some interesting findings on the effects of the alkyl‐chain structure and the special complexation between pyridylpyrazole ligands and Ln III ions. Abstract : The steric effects of the branched chains of a series of alkyl‐substituted pyridylpyrazole ligands on the extraction of Am III and Eu III ions were investigated in HNO3 medium. These ligands exhibit good selective extraction abilities for Am III ions, and the steric effects of the branched chain have a significant impact on the distribution ratios ( D Am and D Eu ) and the separation factor (SFAm/Eu ).